The water defenders how ordinary people saved a country from corporate greed - Broad, Robin; Cavanagh, John 1955- (Beacon Press, 2021)
"A narrative account of how El Salvador's water protectors successfully fought off an international corporation and won an unlikely battle against the World Bank"--